The Interest Of Classic Piano Student In Semarang Music Course (Jurnal Seni Musik, 2021)
The community is very enthusiastic about welcoming music education institutions. There are many people's desire to learn music, especially piano, but not all students have the same interest in learning music. In this case the researchers limited the classical piano participants, with ages 4-6 years. Based on observations, the classical piano learning process has a very detailed learning stage, so that students experience boredom in learning. Seeing this fact, the researcher wanted to know the students' interest in learning classical piano in the Music course in Semarang. The benefit of this research is to know the students' interest in learning classical piano. So that these results can be used for the development of methods, materials, strategies, and media in classical piano learning. The development of this learning component has a beneficial impact on the owners of educational institutions, teachers and students. The result of the discussion is that interest has a great influence on students in learning, because if the material and learning methods are not in accordance with their interests, students will not learn as well as possible, because there is no attraction for them. For students aged 4-6 years, students cannot achieve learning goals just because of interest, but other psychological factors such as intelligence, attention, talent, maturity, readiness, especially motivation that can help return the initial interest, namely learning the piano. Motivation from the closest people, usually parents play an important role in the growth of interest.